2007
DOI: 10.1111/j.1537-2995.2007.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Warm storage of whole blood for 72 hours

Abstract: Storage of whole blood at room temperature for 72 hours leads to marked reductions in pH and DPG, but the observed reduction in PLT function and plasma coagulation factor activity was surprisingly modest compared to literature values. These findings should prompt additional investigation, given their potential importance for whole blood processing and field-expedient transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 33 publications
3
52
0
Order By: Relevance
“…16 Trauma transfusion guidelines were extrapolated from the elective surgery setting, and recent publications suggest that this practice might not be best practice given the acidosis and hypercoagulability associated with hemorrhagic shock. 15,17 Recent reports now indicate that use of a 1:1:1 ratio (ie, equal units of FFP, RBCs, and platelets) of component therapy, mirroring the naturally occurring physiological ratios in whole blood, leads to improved outcomes. 6,18,19 Achieving the rapid administration of a 1:1:1 ratio is challenging for even the most experienced staff in trauma centers and all the more arduous in a mass casualty or disaster situation.…”
Section: Blood Component Therapymentioning
confidence: 99%
“…16 Trauma transfusion guidelines were extrapolated from the elective surgery setting, and recent publications suggest that this practice might not be best practice given the acidosis and hypercoagulability associated with hemorrhagic shock. 15,17 Recent reports now indicate that use of a 1:1:1 ratio (ie, equal units of FFP, RBCs, and platelets) of component therapy, mirroring the naturally occurring physiological ratios in whole blood, leads to improved outcomes. 6,18,19 Achieving the rapid administration of a 1:1:1 ratio is challenging for even the most experienced staff in trauma centers and all the more arduous in a mass casualty or disaster situation.…”
Section: Blood Component Therapymentioning
confidence: 99%
“…Thus, consistent results were not obtained from the samples stored at 258C for 6 h. Therefore, it is certain that the use of blood stored at RT for some time may be undesirable in the examination of platelet function or blood coagulability, though further examination is required to identify the effects of benchtop storage on platelet activities, as recently reported that platelet function and plasma coagulation factor activity during storage of whole blood at RT up to 72 h were surprisingly modest as compared with literature values [38]. Our present study demonstrated that platelet responsiveness is enhanced during cold storage of whole blood for 6 h.…”
Section: Discussionmentioning
confidence: 87%
“…Such a question has only been addressed for whole blood that underwent no further component processing [64]. Apart from a depletion of 2,3-DPG at t = 48 hours when either stored at 19°C or 25°C, small changes in red cell quality with respect to hemolysis, ATP, and free potassium were found.…”
Section: Holding Of Whole Blood Beyond 24 Hoursmentioning
confidence: 93%
“…Thus, a holding time up to 30 hours might be appealing. Both the publication by Hughes et al [64] with a 72-hour storage and by Van der Meer et al [18] with a 24-to 26-hour storage time show that after 24 hours, there is no sudden decline in quality of whole blood or its components, and it should be emphasized that the 24-hour time limit was chosen arbitrarily based on data of the longest storage time that was investigated [6], not by proof that after 24 hours, the units fall off a cliff.…”
Section: Holding Of Whole Blood Beyond 24 Hoursmentioning
confidence: 94%